(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the knowledge and related factors of nurses on preventing catheterassociated urinary tract infections in Huu Nghi Hospital in 2023. Research subjects and methods: A cross-sectional descriptive study was conducted in 17 clinical departments of Huu Nghi hospital. A total 249 out of 270 nurses included in the study. Data were collected by using a structure questionnaire. Results: The percentage of nurses with good knowledge about preventing catheter-associated urinary tract infections is 45.4%. 26.1% of nurses have never been trained in preventing urinary tract infections related to urinary catheters. There was no association between demographic characteristics and good knowledge about preventing catheter-asociated urinary tract infections of nurses at Huu Nghi Hospital. Conclusions: This study shows that the proportion of nurses with good knowledge about preventing catheter-asociated urinary tract infections is quite low. Therefore, regular training classes on preventing urinary tract infections related to urinary catheters should be organized.